Documents on and from the history of economic thought (Amsterdam, Netherlands : Elsevier, 2004)
The book contains two groups of archival materials. The first group includes Edwin Cannan's unsuccessful Codben Essay; an early critque of economics by Eli Ginzberg; introductory notes on the study of the history of economic thought by Warren Samuels; and a memoir by Jacob Warshaw on Thorstein Veblen. The second group contains lecture notes taken by F. Taylor Ostrander in curses given by David Taggart Clark (Williams College), Redvers Opie (Oxford), and Frank H. Knight (Chicago) on the history of economics.
Loans
rua 10/02/15
Keywords: Economics; Economics - history; Economics - methodology